The Effect Of Coaching And Mentoring On Work Motivation By Mediating Employee Self-Efficacy In Sijunjung Regency - Jurniati, Novita; Uripan, Koen Irianto; Soleha, Siti Nur; Endriatmoko, Yosa; Suminar, Lintang (Abadi Institute, 2025)
The era of digital transformation and the complexity of modern organizational performance demands encourage the application of coaching and mentoring as a human resource development strategy. This study analyzes the influence of coaching and mentoring on the work motivation of employees in Sijunjung Regency, with self-efficacy as a mediator. The phenomenon in the field shows a disparity in work motivation between employees who participate in coaching and mentoring programs and those who do not, where the first group has higher self-efficacy and work motivation. A quantitative approach with an explanatory causality method was used on 125 employees through purposive sampling. Data was collected with a 5-point Likert scale questionnaire and analyzed using PLS-based SEM via SmartPLS. The results showed that coaching had a significant effect on work motivation (β = 0.711) and self-efficacy (β = 0.820), while mentoring had a significant effect on work motivation (β = 0.904) and self-efficacy (β = 0.856). Self-efficacy also mediates the influence of coaching and mentoring on work motivation. The research model showed R² 0.754 for self-efficacy and 0.044 for work motivation with a Q² of 0.996, indicating excellent predictive relevance. The findings affirm the important role of self-efficacy as a mediator and make theoretical and practical contributions to human resource development in local governments.